Syndicates, mafias, and extortioners: The guerilla leadership in the higher education institutions in India (Journal of Applied Learning and Teaching, 2025)
With the National Education Policy (NEP) 2020, the higher education systems in India are subjected to rapid infrastructural, cultural, and pedagogical transformations. Due to the rapidity, the quality of the changes is highly questionable, and the quantity of academic productions is getting increasingly incentivized. To institutionalize a fast-paced development syndrome, it is essential to embrace brutal, abusive, devastative, dictatorial, and unauthorized approaches. To ensure that the leadership committees in the higher education institutions are filled with syndicate owners, mafias, and extortioners, who, with fake or paid and purchased degrees, make themselves look qualified for posts like chancellors, pro-chancellors, vice-chancellors, deans, program directors, registrars, and other relevant posts. In the name of quality management and intellectual rigor, they develop ‘stick and whip’ and ‘hire and fire’ systems and compel the staff and students to conform. Anyone failing to conform is subjected to verbal abuse in front of their colleagues and students, penalized with unethical salary cuts, and threatened with job losses. Due to the political connections of the leadership management, the workers and students feel discouraged from taking legal action against them. In this way, the institutions, from an intellectual and knowledge-making resource, are transforming into an operational ground for mafias, syndicates, and extortioners. They treat the staff and students as private money-vending, profitmaking, and promotion-making machines. Through different personal and collective workplace experiences, this opinion piece unfolds how the mafia culture of ‘threat-fire-silence’ is normalized and the irreparable damage it is causing to the higher education culture in India.